Effects of zea mays hairs on physiological parametersheart rate and blood pressure - Chin, Goh Chin (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
Aqueous extract of the Zea mays hairs was screened for its effect on heart rate and blood pressure of albino rats. Twelve rats were divided into two equal groups for two doses of the extract i.e. 50mg/kg and 100mg/kg body weight. The animals were treated for 7 days, 14 days and 28 days and the effects were analyzed. 7 days treatment and 14 days treatment of 50mg and 100mg doses did not show any significant change in heart rate (HR). But 28 days treatment with somg/kg and 100mg/kg was found to decrease the HR significantly. 50mg dose increased systolic blood pressure, diastolic blood pressure and mean arterial pressure significantly after 14 days and 28 days treatment but not in 7 days treatment. 1 oomg dose showed significant increase in systolic blood pressure, diastolic blood pressure and mean arterial pressure in 7 days, 14 days and 28 days treatment with the extract. The pulse pressure did not show any significant change for 50mg dose treatment. But 1 OOmg dose increased pulse pressure significantly after 14 days and 28 days treatment.